The Anxiety-Buffer Hypothesis in the Time of COVID-19: When Self-Esteem Protects From the Impact of Loneliness and Fear on Anxiety and Depression - Rossi, Alessandro; Panzeri, Anna; Pietrabissa, Giada; Manzoni, Gian Mauro; Castelnuovo, Gianluca; Mannarini, Stefania (Frontiers in Psychology, 2020)
Introduction. The coronavirus (COVID-19) disease has spread worldwide, generating intense fear of infection and death that may lead to enduring anxiety. At the same time, quarantine and physical isolation can intensify feelings of dispositional loneliness that, by focusing on thoughts of disconnection from others, can trigger intense anxiety. Anxiety, generated by both fear of COVID-19 and dispositional loneliness, can activate negative expectations and thoughts of death, potentially generating alarming depressive symptoms. However, the Anxiety-Buffer Hypothesis suggests that self-esteem acts as a shield (buffer) against mental health threats – fear and loneliness – thus hampering anxiety and depressive symptoms. Objective: This study aims to test the process – triggered by COVID-19 fear and loneliness – in which self-esteem should buffer the path leading to anxiety symptoms, then to depression. Methods. An observational research design with Structural Equation Models was used. A sample of 1200 participants enrolled from the general population answered an online survey comprising: the Fear of COVID-19 Scale, the UCLA loneliness scale, the Rosenberg Self-Esteem Scale, and the anxiety and depression scales of the Symptom Checklist-90-Revised. Results. Structural equation models showed the link between anxiety symptoms (mediator) with both the fear of COVID-19 and dispositional loneliness (predictors), as well as its association with consequent depressive symptomatology (outcome). In line with the anxiety buffer hypothesis, self-esteem mediated the relation between the predictors and their adverse psychological consequences. Conclusions. Self-esteem represents a protective factor from the antecedents of depression. Targeted psychological interventions should be implemented to minimize the psychological burden of the disease whilst promoting adaptation and positive psychological health outcomes.